Ganglioglioma of the neurohypophysis - Scheithauer, BW (2013)
The normal infundibulum and neurohypophysis consist entirely of neuronal processes, the neuronal cell bodies of which lie within the supraoptic and paraventricular nuclei of the hypothalamus and supportive glial cells or pituicytes. The finding of neurons within the neurohypophysis is exceedingly rare, as are ganglion cell tumors at this site. In this paper, we report a ganglion cell tumor of the neurohypophysis found incidentally at autopsy. Despite chronic hypertension and the finding of some vasopressin immunoreactivity in lesional neurons, the syndrome of inappropriate antidiuretic hormone secretion (SIADH) was excluded on the basis of normal serum sodium levels. The morphologic and immunohistochemical features of the tumor are presented, cytogenetic considerations are discussed, and literature regarding neuronal lesions of the pituitary gland is reviewed